METRICAL EVOLUTION OF MULTIDIMENSIONAL UNIVERSES - Aleksandrov, Yu. V.; Tararoyev, Ya. V. (Одеські астрономічні публікації, 2017)
Fridman's cosmological equations generalisation have been received for arbitrary number of VV-dimension space and their decision in ideal fluid model. The analise of values N influence on the type of universe's evolution have been shown from the point of antropic principle view in particular.